2016
DOI: 10.15361/1984-5529.2016v44n3p338-345
|View full text |Cite
|
Sign up to set email alerts
|

Foliar fertilization with gradual release of shale-based nutrients in strawberry and its effect on yield and compounds with functional potential

Abstract: The aim of this study was to evaluate the influence of a fertilizer matrix of shale-based by-products and shale water as an alternative fertilization on strawberry culture. Were used 16 treatments, which resulted from the combination of three factors levels: cultivar (with two levels: Camarosa and Camino Real), allocated in plot, complementary base fertilization (with two levels: with and without MBR fertilizer matrix at a dose of 2000 kg ha-1), allocated in subplots and foliar fertilization (with four levels:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
4
2
Order By: Relevance
“…Data of number of fruits per plant found in this work were lower than those achieved by Ferreira et al (2019), which obtained averages for the number of fruits per plant of 50.5, 45.4 and 31.8 for the Benicia, Monterey and Albion cultivars, respectively, and those obtained by Costa et al (2018), which obtained averages of number of fruits oscillating between 24.6 and 42.67 fruits per plant, evaluating twelve cultivars, among them Albion, Aromas and Camarosa. However, the number of fruits per plant found in this work for the cultivars Camino Real and Camarosa was higher than those obtained by Araújo et al (2016), which obtained averages of 15.28 fruits plant -1 (Camino Real) and 15.77 fruits plant -1 (Camarosa). Environmental factors, such as planting time (Ruan et al 2011;Ariza et al, 2012), temperature and relative humidity fluctuations (Costa et al, 2016), type and quality of the planting material (Ruan et al, 2011), cultivation (Ariza et al, 2012;Araújo et al, 2016) and diseases incidence (Oliveira & Bonow, 2012) may cause these oscillations in the variable number of fruits per plant.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…Data of number of fruits per plant found in this work were lower than those achieved by Ferreira et al (2019), which obtained averages for the number of fruits per plant of 50.5, 45.4 and 31.8 for the Benicia, Monterey and Albion cultivars, respectively, and those obtained by Costa et al (2018), which obtained averages of number of fruits oscillating between 24.6 and 42.67 fruits per plant, evaluating twelve cultivars, among them Albion, Aromas and Camarosa. However, the number of fruits per plant found in this work for the cultivars Camino Real and Camarosa was higher than those obtained by Araújo et al (2016), which obtained averages of 15.28 fruits plant -1 (Camino Real) and 15.77 fruits plant -1 (Camarosa). Environmental factors, such as planting time (Ruan et al 2011;Ariza et al, 2012), temperature and relative humidity fluctuations (Costa et al, 2016), type and quality of the planting material (Ruan et al, 2011), cultivation (Ariza et al, 2012;Araújo et al, 2016) and diseases incidence (Oliveira & Bonow, 2012) may cause these oscillations in the variable number of fruits per plant.…”
Section: Resultscontrasting
confidence: 85%
“…However, the number of fruits per plant found in this work for the cultivars Camino Real and Camarosa was higher than those obtained by Araújo et al (2016), which obtained averages of 15.28 fruits plant -1 (Camino Real) and 15.77 fruits plant -1 (Camarosa). Environmental factors, such as planting time (Ruan et al 2011;Ariza et al, 2012), temperature and relative humidity fluctuations (Costa et al, 2016), type and quality of the planting material (Ruan et al, 2011), cultivation (Ariza et al, 2012;Araújo et al, 2016) and diseases incidence (Oliveira & Bonow, 2012) may cause these oscillations in the variable number of fruits per plant.…”
Section: Resultscontrasting
confidence: 85%
“…The highest averages for total production per plant were obtained with the largest spacing between plants (30 cm), 540.45 g plant -1 in the 2018/2019 harvest and 685.50 g plant -1 in the 2019/2020 harvest ( Figure 1B). The average productions in the two evaluated crops were below the potential of the cultivar Pircinque, 1 kg per plant, considered appropriate to provide good profitability to the producer [26], and also when compared to another study that obtained the average production of 848.9 g plant -1 , testing four cultivars in suspended cultivation [44]. In both agricultural harvests of 2018/2019 and 2019/2020, there was a decrease in productivity due to the increase in spacing between plants ( Figure 2A).…”
Section: Productive Parametersmentioning
confidence: 73%
“…The number of fruits was higher in the 2019/2020 harvest than in the 2018/2019 harvest. These variations in the number of fruits per plant are mainly due to factors such as cultivars, date of planting [42,43], cultural practices [43,44,45], and also by temperature fluctuations, water regime, and incidence of diseases during the growing seasons [12,46].…”
Section: Productive Parametersmentioning
confidence: 99%
“…Other authors re-ported variations from 21.3 to 44.9 fruits in soil and substrate cultivations [48]. These variations in the number of fruits per plant are mainly due to factors such as cultivar, the date of planting [40,49], cultural practices [40,50,51], and by temperature fluctuations, water regime, and the incidence of diseases during the growing seasons [14,52]. Other authors reported the increase in the number of fruits verified in the present study due to increased spacing between plants and in several cultures, such as larger fruit vegetables [53,54].…”
Section: Productive Parametersmentioning
confidence: 98%